Inventories of Psychological Skills for Athletic Clubs and School Life. Issue 1 (February 2014) - Ueno, Kohei
Some students who participate in athletic activities transfer the skills acquired in a sports context into other areas of life, while others do not. To identify the specific skills that are transferred or not from sports to the school environment, two inventories were developed: the "Psychological Skills Inventory for Athletic Clubs" and the "Psychological Skills Inventory for School Life." These inventories enable a comparison of skills in a sport context with skills in a school context. In the first stage, 307 Japanese first-year university students who had participated in high school athletic clubs volunteered to take part in a survey to develop these inventories. Analyses indicated that both inventories comprised identical subscales of intrapersonal and interpersonal skills. In the second stage, the reliability and validity of these inventories was confirmed for 531 Japanese high school students who were members of athletic clubs for sports such as soccer and baseball.